2020
DOI: 10.1186/s12913-019-4883-6
|View full text |Cite
|
Sign up to set email alerts
|

Remuneration systems of community health workers in India and promoted maternal health outcomes: a cross-sectional study

Abstract: Background: This study assessed the association of remuneration systems of paid-for-performance Accredited Social Health Activists (ASHAs) and salaried Anganwadi workers (AWWs) on seven maternal health outcomes in four states in India: Andhra Pradesh (AP), Chhattisgarh, Odisha (Orissa), and Uttar Pradesh (UP). Methods: The cross-sectional study surveyed mothers of children aged 6-23 months. A total of 3455 mothers were selected via multistage cluster sampling. The seven health outcomes related to the community… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Studies from a wide range of settings have shown that greater access to Frontline Health Workers (FHWs) or Community Health Workers (CHW) can greatly improve maternal and child health care utilisation and outcomes. FHWs play an important role in disseminating community-based health information and encouraging the utilisation of MCH and family planning services [13,[17][18][19][20][21][22][23]. FHWs directly interact with women and their family members, particularly in poor and remote disadvantaged communities [21,[23][24][25].…”
mentioning
confidence: 99%
“…Studies from a wide range of settings have shown that greater access to Frontline Health Workers (FHWs) or Community Health Workers (CHW) can greatly improve maternal and child health care utilisation and outcomes. FHWs play an important role in disseminating community-based health information and encouraging the utilisation of MCH and family planning services [13,[17][18][19][20][21][22][23]. FHWs directly interact with women and their family members, particularly in poor and remote disadvantaged communities [21,[23][24][25].…”
mentioning
confidence: 99%
“…33 However, a recent study conducted in four Indian states showed that ASHAs’ visits to beneficiaries were not more strongly associated with outcomes for which they were paid than outcomes for which they were unpaid. 34 The Home Based Newborn Care initiative, rolled out in Bihar after 2014, provided incentives to ASHAs for postnatal follow-up visits and tracking of low birthweight newborns. 35 The increased emphasis on postnatal care, while important, might have also affected the time ASHAs had for household visits to pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1975, Anganwadi workers (AWWs) and auxiliary nurse-midwives (ANMs) have been the major CHWs in India; they focus on women and child health (44). In addition, Accredited Social Health Activists (ASHAs) were introduced in 2005 by the National Rural Health Mission (NRHM) to improve the outreach and coverage of health services in rural areas.…”
Section: Introduction and Aim Of The Studymentioning
confidence: 99%
“…In addition, Accredited Social Health Activists (ASHAs) were introduced in 2005 by the National Rural Health Mission (NRHM) to improve the outreach and coverage of health services in rural areas. Each village in India is supposed to have at least one ASHA and one AWW (44). ASHAs represent a new kind of CHW; they supplement the work of AWWs and ANMs by also addressing noncommunicable diseases (NCDs) (45).…”
Section: Introduction and Aim Of The Studymentioning
confidence: 99%
See 1 more Smart Citation